A computational method for model reduction in index-2 dynamical systems for Stokes equations. (1st October 2021) - Chkifa, A.; Hamadi, M.A.; Jbilou, K.; Ratnani, A.
Abstract: Our aim through this paper is to describe a Krylov based projection method in order to reduce high-order dynamical systems. We focus on differential algebraic equations (DAEs) of index-2 that arise from spatial discretization of Stokes equations. An efficient algorithm based on a projection technique onto an extended block Krylov subspace that appropriately allows us to construct a reduced order system is described. Numerical results are provided to confirm the performance of the derived method compared with other known ones.